Interactions between rice resistance to planthoppers and honeydew-related egg parasitism under varying levels of nitrogenous fertilizer - Peñalver-Cruz, Ainara; Horgan, Finbarr G. (MDPI, 2022)
Host plant resistance is the most researched method for the management of planthoppers and leafhoppers in tropical rice. For optimal effects, resistance should be resilient to fertilizer inputs and work in synergy with natural enemies. In field plot experiments, we examined how rice resistance and fertilizer inputs affect mortality of planthopper and leafhopper eggs by hymenopteran parasitoids. We used IR62 as a variety with resistance to Nilaparvata lugens (Stål) [BPH], Sogatella furcifera (Horváth) [WBPH] and Nephotettix virescens (Distant) [GLH], and IR64 as a susceptible control. The herbivores were more abundant during wet season sampling in low-nitrogen plots. During this study, parasitoids killed between 31 and 38% of BPH eggs and 24 and 52% of WBPH eggs during four days of field exposure. Parasitism, mainly due to Oligosita spp., was generally higher in high-nitrogen and IR64 plots. Similar densities of eggs in exposed plants suggest that these trends were mediated by semiochemicals and therefore support the Optimal Defense Hypothesis. Honeydew from BPH on IR62 had more xylem-derived wastes than honeydew on IR64. We applied honeydew from both varieties to sentinel plants. Parasitism by Anagrus spp. was higher on plants of either variety treated with honeydew derived from IR62; however, the effect was only apparent in high-nitrogen plots. Results suggest that Anagrus spp., by responding to honeydew, will counter the nitrogen-induced enhancement of planthopper fitness on resistant rice.